Congenital diaphragmatic hernia and complete tracheal rings: Repair on ECMO - Sasha J. Tharakan; Natalie E. Rintoul; Luv R. Javia; Christopher E. Mascio; James T. Connelly; Kha M. Tran; William H. Peranteau; Anne Ades; N. Scott Adzick; Holly L. Hedrick (Elsevier, 2015)
A term newborn female presented with prenatally diagnosed congenital diaphragmatic hernia and postnatally diagnosed complete tracheal rings and tracheal stenosis. Initially, the spells associated with tracheal stenosis were misdiagnosed as pulmonary hypertension. Bronchoscopy showed a critically narrowed airway, and veno-arterial ECMO stabilized the baby for further workup. The endotracheal tube was removed while on ECMO to avoid further injury to the airway. Staged CDH repair followed by slide tracheoplasty were performed on ECMO. The multidisciplinary approach included neonatology, general surgery, otolaryngology, cardiac surgery and anesthesiology.